Self-healing characteristics of bituminous mastics using a modified direct tension test. (January 2014) - Qiu, Jian; van de Ven, Martin; Wu, Shaopeng; Molenaar, André; Yu, Jianying
Cracking is one of the main distresses responsible for the service life reduction of asphalt pavement. On the contrary, self-healing is a process that reverses to cracking and increases the service life. Understanding of the cracking and healing behavior of bituminous materials is very important for service life predictions. Instead of a complex and time-consuming fatigue test, a modified direct tension test with a loading–healing–reloading procedure was developed in this article to characterize the cracking and healing behavior of bituminous mastics. A displacement-controlled loading was applied to obtain damaged specimens with different crack sizes at various postpeak elongations. After unloading and healing, the reloading was applied to quantify the healing behavior under different conditions. The healing behavior is very dependent on rest periods, crack phases, and material types. A clear difference in self-healing property between a polymer-modified bituminous mastic and a conventional penetration grade bituminous mastic was observed for different phases of crack. As a result, the modified direct tension test is believed to be an effective tool for characterizing the self-healing capability of bituminous mastics.